DIMENSI HUBUNGAN NEGARA, POLITIK DAN PENDIDIKAN - Kasful Anwar Us (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2010)
State, politics, and education is a set of unseparated dimensions of human life. Those three aspects have a close relation and sinergyze each others. State is the organization which has legitimation and politics is a tools to reach a goals had been planned. Education is the process to humanize human resources in the country. Education, sometimes, legitimize ruling elite policy. But it sometimes also play important role in guiding the state finding democratic spirit and as a tool to achieve people’s rights.